AN ANALYSIS OF DISCOURSE MARKERS IN THE ARTICLES ON HAMLET DRAMA WRITTEN BY ENGLISH EDUCATION STUDENTS AT UNIVERSITY OF MATARAM - Frida Anjani Hidayat; Baharuddin Baharuddin; Muhammad Isnaini (Program Studi Pendidikan Bahasa Inggris, 2021)
This study is targeting at portraying the sorts and the errors of discourse markers made in the articles on Hamlet drama composed by the 6th semester students of English education program at University of Mataram in the academic year 2019/2020. The technique of conducting this investigation is a blended strategy or mix of qualitative and quantitative techniques. The data were gathered from 26 students’ articles. The result of this study showed that all the types in three functional classes of discourse markers by Bruce Fraser (2009) were used by students in their articles. They are Elaborative Discourse Markers with total number of occurrences 200 times (43.20%), Contrastive Discourse Markers with total number of occurrences 169 times (36.50%), and Inferential Discourse Markers with total number of occurrences 94 times (20.30%). The researcher found that Elaborative Discourse Markers are most frequently employed by students to elaborate the ideas. Furthermore, there are some errors in student’s articles related to Kao and Chen's theory (2011) about the six types of misuse patterns. Turns out three of six misuse patterns occur in students’ articles such as distraction, wrong relation, and semantic incompletion. There are no surface logicality, non-equivalent exchange, and overuse occurred in students’ articles.